The effect of metallic addition on mechanical property of aluminum (LM6) alloy - Ahmad, Roslee (Trans Tech Publications Inc, 2013)
This article investigates the effects of addition of alloying element on the impact toughness of as-cast aluminum (LM6) alloy. Presence of 0.1 wt.% Cr increases the toughness up to 38%. In fact the sharp tips Fe intermetallics which have needle shape act as stress raisers with a general reduction of the ductility and ultimate tensile strength. On the other hand by increasing the Cr content in the base alloy the size distribution of the compounds becomes more spread. Therefore addition of Cr improves toughness impact by two mechanisms. First eliminating harmful β-intermetallics and second providing microstructure with more spread particles.